DETERMINANTS OF THE DOWRY: FINDING FROM IFLS EAST - Kurniawan, Randi (Fakultas Ekonomika dan Bisnis, Universitas Diponegoro, 2019)
This study aims to analyze the factors that influence the amount dowry/wedding gift in marriage. The study used female individuals (n=1,532) from The Indonesia Family Life Survey (IFLS) East data who lived in 7 provinces in eastern Indonesia. Using multivariate regression, the results of this study found that the economic status and the level of education of female before marriage have positive effect on the amount of dowry. Geographical, ethnic, and religious factors can also explain the variation of dowry. Married female in East Nusa Tenggara province, Muslim’s female, and Bugis-Makassar-Toraja’s female receive higher dowry than other counterparts. The results of this study provide evidence regarding the reasons for the high dowry in several communities in eastern part of Indonesia.